66.4k views
5 votes
Can you show me the steps to factor out 8x^3 - 27y^3?

User Abukaj
by
5.8k points

1 Answer

2 votes


(2x-3y)(4x^2+6xy+9y^2) is the factored form of
8x^3-27y^3

Solution:

We have to factor the given expression


8x^3-27y^3

We can use the algebraic identity to factor the given expression


a^3-b^3=(a-b)(a^2+ab+b^2)

Lets make the given expression in form of
a^3-b^3


8x^3-27y^3=(2)^3(x)^3-(3)^3(y)^3


8x^3-27y^3=(2x)^3-(3y)^3

Now apply the algebraic property in above expression

Here, a = 2x and b = 3y

Therefore,


(2x)^3-(3y)^3=(2x-3y)((2x)^2+(2x)(3y)+(3y)^2)


(2x)^3-(3y)^3=(2x-3y)(4x^2+6xy+9y^2)

Thus the given expression is factored out

User Ryan Lavelle
by
5.8k points